Impact attenuation of protective boxing and taekwondo headgear - O`Sullivan, D. M.; Fife, G. P. (European Journal of Sport Science, 2016)
This study aimed to compare the impact attenuation performance of boxing and taekwondo headgear in terms of peak linear and rotational acceleration. To measure the impact attenuation of headgear, a standardized (American Society for Testing and Materials (ASTM) F-2397) martial arts headgear striker was used to impart impacts to a 50th Percentile Male Hybrid III Crash Test Dummy head and neck complex. Two boxing (Adidas and Greenhill) and two taekwondo (Adidas and Nike) headgear, approved by the Association Internationale de Boxe Amateur and the World Taekwondo Federation (WTF), were selected. Each of the selected headgear was fitted to the Hybrid III head and subsequently subjected to five impacts at the front and side with a maximum impact interim time of 60 seconds by the rotating striker at 8?±?0.3 m/s. Linear and rotational acceleration were recorded at 10,000 Hz. There were significant interactions of the impact location and brand on the rotational acceleration, F(3,40)?=?6.7, p?<?.05. There were significant main effects of both impact location F(1,40)?=?9.07, p?<?.05 and headgear brand F(3,40)?=?9.9, p?<?.05 on the linear acceleration. Pairwise comparisons show significant differences between the front and side for both linear and rotational acceleration. The headgear tested failed the ASTM high impact test requirement to reduce the linear acceleration to below a threshold of 150 g. Further development of headgear to reduce impact linear and rotational acceleration magnitudes should be called for by the relevant sport governing bodies and initiated by headgear manufactures.